THE OCCURRENCE OF DIFFERENT TYPES OF DEPRESSION IN PATIENTS WITH CERVICAL CANCER - conic, irena; Conic, Irena; Stojnev, Slavica; Tosic Golubovic, Suzana; Petkovic, Ivan; Cvetanovic, Ana; Krtinic, Dane; Radic, Milica; Milovic Kovacevic, Marijana; Zivadinović, Aleksandar; Simic, Dusan (Acta medicae Medianae, 2026)
When a person is diagnosed with a severe and life-threatening disease, experiences sudden hospitalization, undergoes surgical intervention or faces other treatment options threatening their bio-psycho-social integrity, it can create a stressful situation that may result in an acute stress reaction or adjustment disorders. The global aim of the research was to examine the impact of the type of cervical cancer therapy on the psychological status of patients and the occurrence of depression. The basic principle of the research was a comparative analysis of the results obtained using instruments to assess the degree of depression in the experimental and control groups. Within the first experimental group, a comparison was made between patients who underwent surgery and postoperative chemoradiation. Within the second experimental group, a comparison was made between patients who did not undergo surgery, but received radical chemoradiation therapy. The following research instruments were used: semi-structured psychiatric interview, gynecological parameters—local findings and stage of the disease, the Hamilton scale for depression. Univariate logistic regression analysis showed that patients before surgery (OR = 24.17; 95% PI: 4.81–121.57 and p < 0.001) and patients before radical chemoradiation (OR = 45.99; 95% PI: 8.70–243.15 and p < 0.001) had a significantly higher risk of depression than women from the control group. Radical hysterectomy is accompanied by an increase in depression in the preoperative period as well as after surgical treatment. Radical chemoradiation leads to an increase in depression to a greater degree compared to radical hysterectomy in the period before and after the treatment.